Study of Biomechanical Risk Factors for Musculoskeletal Disorders in the Bakery Business Based on ART and OCRA Index - Mohammad Hossein Beheshti; Mostafa Jafarizaveh; Seyyed Ehsan Samaei; Shahram Vosoughi; Maryam Borhani Jebeli; Ghasem Zia (Archives of Occupational Health, 2021)
Background:Bakery workers, Beacause of their nature, are at risk of musculoskeletal disorders caused by ergonomic factors. The purpose of this study was to evaluate the biomechanical risk factors for musculoskeletal disorders in bakery workers. Methods: In the current study, all tasks of sangak, taftoon, and lavash bakery in Gonabad were selected based on the census method. Next, Hierarchical Task Analysis (HTA) method was used for task analysis, and the job was degraded to tasks, actions, and movements. For the following step, the ART and OCRA method was implemented to identify common risk factors in repetitive tasks that can contribute to developing musculoskeletal disorders of upper limbs. Analysis of the results in this study was performed using SPSS 17. Results: According to the results study, the ART and OCRA index score for shater and chonegir tasks for all three kinds of bakeries is at high risk (red zone). In ART index score of arm movements, repetition, force, head/neck posture, and back posture for shater and choonegir task in lavash and taftoon bakery and shater task in sangak bakery is in its maximum levels. This reflects the level of red risk and indicates that in these tasks, fast arm movements, repetition, force, head/neck posture, and back posture are recognized as major occupational risk factors in these tasks. Conclusion: The results showed that the risk of musculoskeletal disorders owing to repetitive tasks is relatively high in the bakery and ergonomic interventions are required to redesign the job. This study shows the use of the ART method as a practical, applicable, easy, and convenient method for evaluation and ergonomics interventions in repetitive work tasks.